Evaluation of apically extruded debris during removal of gutta-percha and Resilon™ using different instrumentation techniques - Pešić, Dragana; Melih, Irena; Kolak, Veljko; Nikitović, Ana; Jakovljević, Ankica (Vojnosanitetski pregled, 2020)
Background/Aim. Apical extrusion of material is considered as one of the very important factor for endodontic treatment success. Microorganisms, necrotic tissue, filling material and irrigants, which can be extruded apically during endodontic retreatment, may jeopardize the success of the therapy. The aim of this in vitro study was to quantitatively evaluate the amount of apically extruded debris during endodontic retreatment of teeth obturated with two different materials, using one hand and three rotary instrumentation techniques. Methods. Ninety-six extracted single-rooted teeth were endodontically treated and enlarged to size 40 using BioRaCe system, and then randomly divided into 8 groups of 12 specimens each. Half of the specimens were obturated with gutta-percha and AH Plus® sealer and another half with RealSeal SE system, using lateral condensation technique. Retreatment was performed using: Hedström files; ProFile rotary files; ProTaper Retreatment system and D-RaCe system. Apically extruded debris was collected in pre-weighed Eppendorf tubes and evaluated using an electronic microbalance. Data were analyzed statistically using t-test and analysis of variance. Results. In the AH Plus/gutta-percha group, all tested rotary instruments gave significantly less extruded debris compared with Hedström files (p < 0.05). In theRealSeal group, there was significant difference between D-RaCe and Hedström instruments (p < 0.05). Conclusion. All retreatment techniques resulted in apical extrusion. D-RaCe system produced significantly less extruded debris compared to hand files. No significant difference was found when comparing two instruments specially designed for retreatment: D-RaCe and ProTaper systems.